DETERMINANTS OF CUSTOMER LOYALTY - eva indah; abdul nasser hasibuan; Ali Hardana; rahmat annam (Journal Of Sharia Banking, 2021)
This study aims to determine the effect of customer satisfaction and bank image on customer loyalty at Pt. Bank Muamalat Indonesia, Tbk., Panyabungan Sub-Branch Office. The creation of customer satisfaction and a good bank image is an advantage for banks. Satisfaction is a good basis for customers to repeat the use of related bank services so that these customers become loyal. This research is a quantitative study, data obtained from questionnaires. The sample collection technique uses the Slovin formula to obtain a sample of 83 customers. Data analysis using multiple linear regression. The results showed that customer satisfaction partially affected customer loyalty and the image of the bank affected customer loyalty. Then simultaneously customer satisfaction and the image of the bank together have a significant and significant effect on customer loyalty.